Detection of ESBL-producing Escherichia coli carrying blaCTXM-15 in magnificent frigatebird (Fregata magnificens) from Brazil: a one health perspective - Pribul, Bruno Rocha; da Silva Nascimento, Letícia; Marinato, Carlos Eduardo Gaspar; Silveira, Melise Chaves; Rodrigues, Daiana Cristina Silva; Sued-Karam, Bruna Ribeiro; Serwy, Daniel Miceli; Ogrzewalska, Maria; Bueno, Marina Galvão; D’Alincourt Carvalho-Assef, Ana Paula; de Souza, Miliane Moreira Soares; Rocha-de-Souza, Cláudio Marcos (Frontiers in Microbiology, 2025)
BackgroundWild birds are increasingly recognised as sentinels for antimicrobial resistance (AMR) in environments impacted by human activity, yet the role of seabirds in the dissemination and maintenance of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli in Brazil remains unclear.MethodsCloacal swabs were collected from fifteen magnificent frigatebirds (Fregata magnificens) from the Cagarras Islands, a coastal archipelago. Bacterial isolation was performed using MacConkey agar supplemented with ceftriaxone, followed by identification using MALDI-TOF MS. Antimicrobial susceptibility testing was conducted using the disc diffusion method, and PCR screening was performed for ESBL genes. WGS and bioinformatics analysis were employed to characterise the isolate.ResultsOne ceftriaxone-resistant E. coli isolate was recovered from an adult female bird. The isolate was identified as sequence type ST5614 and serotype O27:H14, carrying the blaCTX-M-15 gene on an IncB/O/K/Z plasmid closely related to those described in human isolates. The strain showed resistance to multiple antimicrobials and harboured additional resistance genes including tet(A), sul1, sul2, mph(A), qnrS1, mrx(A), aph(3”)-Ib, aph(6)-Id, and ant(3”)-Ia.ConclusionDetection of blaCTX-M-15 in F. magnificens may reflect the movement of clinically significant resistance genes at the human–wildlife interface, underscoring the value of seabirds as sentinels for environmental AMR surveillance. The findings highlight the interconnectedness of environmental, animal, and human health and reinforce the importance of wildlife surveillance in One Health AMR strategies.